Evaluation of hair cotinine and toxic metal levels in children who were exposed to tobacco smoke. Issue 4 (18th February 2020) - Gunay, Fatih; Cullas Ilarslan, Nisa Eda; Bakar‐Ates, Filiz; Deniz, Kiymet; Kadioglu, Yusuf Kagan; Kiran, Sibel; Bakirarar, Batuhan; Cobanoglu, Nazan
Abstract: Tobacco or tobacco products (TTP) are harmful because they contain nicotine and some heavy metals. In this study, it was aimed to evaluate whether the responses of parents to questionnaires were compatible with the hair cotinine levels of their children, and to investigate whether exposure to environmental tobacco smoke (ETS) and living conditions increased the levels of cotinine, lead (Pb), arsenic (As), and cadmium (Cd) in the hair samples of the children. Questionnaires were administered to the parents questioning household consumption of TTP and living conditions. Children were grouped as "exposed to ETS" (E‐ETS) and "not exposed to ETS" (NE‐ETS). This grouping was performed through a questionnaire‐based evaluation, and a hair cotinine cut‐off value‐based evaluation. According to the questionnaire‐based evaluation, there were no significant differences in hair Pb, As, and Cd levels between the groups ( P ‐values: .337, .994, and .825, respectively). The hair cotinine of the E‐ETS group was higher (0.24 ± 0.21 vs 0.22 ± 0.15 ng/mg), but the difference was not statistically significant ( P = .317). According to the cotinine evaluation, cotinine, Pb, and As levels were statistically higher in the E‐ETS group ( P < .001, <.001, and .036, respectively), but there was no statistical difference between the groups in terms of Cd levels ( P = .238). Our results showed that exposure to ETS increased the levels of cotinine, Pb, and As in the hair samples of children, and the questionnaire responses of the parents about their smoking habits might not be compatible with the hair cotinine levels of the children.